Is ghrelin synthesized in the central nervous system? - Cabral, Agustina Soledad (2017)
Ghrelin is an octanoylated peptide that acts via its specific receptor, the growth hormone secretagogue receptor type 1a (GHSR-1a), and regulates a vast variety of physiological functions. It is well established that ghrelin is predominantly synthesized by a distinct population of endocrine cells located within the gastric oxyntic mucosa. In addition, some studies have reported that ghrelin could also be synthesized in some brain regions, such as the hypothalamus. However, evidences of neuronal production of ghrelin have been inconsistent and, as a consequence, it is still as a matter of debate if ghrelin can be centrally produced. Here, we provide a comprehensive review and discussion of the data supporting, or not, the notion that the mammalian central nervous system can synthetize ghrelin. We conclude that no irrefutable and reproducible evidence exists supporting the notion that ghrelin is synthetized, at physiologically relevant levels, in the central nervous system of adult mammals.